Plan de negocios para producción y exportación de vino artesanal de guanábana a Alemania - Guamán Obando, Rita Alejandra (2020)
The signing of the Multipart agreement between Ecuador and the European Union, offers multiple advantages for the export of Ecuadorian products to the countries that make up the EU, in the case of alcoholic beverages these are currently taxing a 0 percent tariff allowing the income of Ecuadorian wines are more competitive, since their price will not increase when entering these countries. This being the main opportunity that we want to take advantage of in this project, whose objective is the production of soursop artisanal wine in Ecuador, to later commercialize it in Germany, which is the country that consumes the most HI of wine consumed in the world, and that Despite being a producer and importer of this beverage, the demand is not satisfied, especially considering that 90 percent of Germans between 18 and 65 years of age consume wine at least once a day, since they are usually accompanied by lunch and dinner, as well as meetings with friends and family. When conducting a survey of the target audience, 100 percent were interested in soursop wine, because they consider it something new because they do not have an equal one in their country, especially one that promises to be sweet, as are their preferences. Considering these factors, it was determined that the proposed business plan is viable and profitable with a NPV of 139.518,85 dollars an IRR of 29.69 percent earnings of 1.95 dollars for each dollar invested, and an investment recovery period of approximately 4 years.